Microfibrous borate bioactive glass dressing sequesters bone-bound bisphosphonate in the presence of simulated body fluid1. Issue 6 (14th February 2015) - Pramanik, Chandrani; Wang, Tianda; Ghoshal, Sushanta; Niu, Lina; Newcomb, Bradley A.; Liu, Yaodong; Primus, Carolyn M.; Feng, Hailan; Pashley, David H.; Kumar, Satish; Tay, Franklin R.
<x xml:space="preserve">Abstract</x> Release of bone-bound bisphosphonates by borate bioactive glass dressings may be useful for managing bisphosphonate-related osteonecrosis of the jaw (BRONJ).